2022
DOI: 10.1111/ases.13075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short‐term outcomes of robotic‐assisted and conventional laparoscopic surgery for rectal cancer: A propensity score‐matched analysis

Abstract: Introduction:The advantages of robotic-assisted laparoscopic surgery (RALS) for rectal cancer remain controversial. This study clarified and compared the short-term outcomes of RALS for rectal cancer with those of conventional laparoscopic surgery (CLS). Methods: The records of 303 consecutive patients who underwent RALS or CLS for rectal adenocarcinoma between November 2016 and November 2021 were analyzed using propensity score-matched analysis. After matching, 188 patients were enrolled in our study to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Because patients who are transferred from minimally invasive surgery to open surgery are more prone to postoperative complications and local recurrence, the conversion rate of surgery is one of the key indicators for demonstrating the progress of surgical technology[ 11 ]. In this study, there was no conversion to open surgery in either group, which is similar to the findings of Yamanashi et al [ 12 ]. This benefits from the rich expertise of the surgical team in treating rectal cancer, which also proves the surgical safety of robot-assisted surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Because patients who are transferred from minimally invasive surgery to open surgery are more prone to postoperative complications and local recurrence, the conversion rate of surgery is one of the key indicators for demonstrating the progress of surgical technology[ 11 ]. In this study, there was no conversion to open surgery in either group, which is similar to the findings of Yamanashi et al [ 12 ]. This benefits from the rich expertise of the surgical team in treating rectal cancer, which also proves the surgical safety of robot-assisted surgery.…”
Section: Discussionsupporting
confidence: 92%
“…To date, some studies that incorporated propensity score matching have reported on the short-term outcomes of RARS [24][25][26] ; however, few have focused on anal preservation. In a single-institution, retrospective study, Kojima et al 27 showed that, compared with LARS, RARS achieved a significantly greater rate of low anterior resection with sphincter preservation in patients with ultralow rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, laparoscopic surgeries, while generally requiring less anesthesia than open procedures, may still necessitate more compared to robotic-assisted surgeries due to factors such as pneumoperitoneum maintenance and the need for prolonged operative times. Anesthesia considerations in open surgeries, given the invasiveness and potential for greater tissue disruption, often involve higher doses and more comprehensive pain management strategies [ 41 ]. These findings underscore the nuanced approach required in tailoring anesthesia protocols to the specific demands of each surgical modality, emphasizing the importance of individualized patient care [ 39 , 42 ].…”
Section: Advantages Of Using Robotic-assisted Surgery In Neonates And...mentioning
confidence: 99%